Micro-chemical and radiological characterization using ?-spectrometry and WDXRF spectrometry and annual effective dose of cigarette tobaccos - Sogot, O.; Kocaer, A. F.; Zorer, O. Selcuk; Ozdemir, Y.; Dogru, M. (Elsevier, 2014)
Several kinds of cigarette tobacco were analyzed to determine contents of essential elements, natural and artificial radioactivity. The contents of essential elements and radionuclides were determined by WDXRF and gamma spectrometry, respectively. Samples were analyzed by WDXRF technique for the following elements; Al, P, S. Cl, K, Ca, Ti, Mn, Fe, Ni, Cu, Zn, As, Br, Stand In in cigarette tobaccos. In the contents of essential elements, the mean amounts of I< (48.891%) and Ca (38.358%) have the highest contents in the cigarette tobaccos. The radionuclide activity concentrations of (CS)-C-137, (238)u, Th-232, K-40 and Sr-90 were measured in cigarette tobaccos. According to radioactivity concentration results, U-238 ranged between 0.549 and 6.181 Bq/kg; Th-232 between 0.160 and 3.748 Bq/kg; Cs-137 between 0.023 and 2.355 Bq/kg; Sr-90 between 0.019 and 2.305 Bq/kg and K-40 between 2.894 and 56.333 Bq/kg. It was concluded that the annual effective dose due to inhalation for adults (smokers) for U-238 varied from 4.97 to 55.94 mu Sv/y (average 28.04 mu Sv/y), while for Th-232 from 12.48 to 292.41 mu Sv/y (average 138.65 mu Sv/y) and for K-40 from 18.97 to 370.45 nSv/y (average 139.83 nSv/y). The annual effective dose from Cs-137 and Sr-90 of Chemobyl origin varied from 0.70 to 71.29 nSv/y (average 29.86 nSv/y) and from 9.49 to 1150.93 nSv/y (average 415.29 nSv/y), respectively. (c) 2014 Elsevier B.V. All rights reserved.
Keywords: WDXRF; Radionuclide; Trace element; Tobacco; Gross radioactivity; Annual effective dose